The gut microbiota in infants of obese mothers increases inflammation and susceptibility to NAFLD - Taylor K. Soderborg (Nature Portfolio, 2018)
Infants born to obese mothers have altered microbiome and increased risk of obesity and NAFLD. Here the authors establish causality by showing that maternal obesity-shaped infant gut microbiome induces macrophage dysfunction, inflammation, and diet-induced metabolic disease in germ-free mice.